ANALISIS KORELASI INDEKS BIAS DENGAN KONSENTRASI SUKROSA BEBERAPA JENIS MADU MENGGUNAKAN PORTABLE BRIX METER - Putri Parmitasari; Eko Hidayanto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
Sucrose concentration of honey solution has been analized by using Portable Brix Meter to determine its refractive index using Abbe refractometer. The materials used are honey randu solution, honey pollen, honey flora, honey klengkeng, honey karet, honey rambutan, white honey royal jelly, and honey kapuk with a concentration of 10 % until 50 %. The meansurement of sucrose concentration was performed by droping a few of sample solution above the sample table in this equipment. The content of sucrose is displayed digitally with units brix (%). The concentration of sucrose solution proportional to the refractive index. The increase of concentration of sucrose solution will increase the refractive index. Correlation between the concentration of sucrose solution with refractive index by the equation n = 0,001C + 1,334 (R2 = 0,9972), n = 0,001C + 1,354 (R2 = 0,9919), n = 0,0015C +1,334 (R2 = 0,9999), n = 0,002C + 1,333 (R2 = 0,9817), n = 0,0015C + 1,334 (R2 = 0,9819), n = 0,002C + 1,328 (R2 = 0,9969), n = 0,002C + 1,329 (R2 = 0,9936), n = 0,002C + 1,322 (R2 = 0,9830). Refractive index of sucrose solution can be determined from its concentration.Keywords : refractive index, concentration of sucrose, honey, portable brix meter